Social commerce behavior among university students in Malaysia - Mohamed Razi, Mohamed Jalaldeen; Mohd Tamrin, Mohd Izzuddin; Hussin, Husnayati (School of Computing, Univerisiti Utara Malaysia, 2017)
The aim of this study is to investigate the consumer behavior of current Malaysian university students in the social commerce environment. A hypothetical conceptual framework was formulated based on proven theories and previous works. Data were collected from 209 students from a Malaysian public university using self-administered online questionnaire. Though the linear regression supports all proposed hypotheses, the stepwise regression results are mixed. Closeness and familiarity among social network friends are the predictors of trust, while trust and enjoyment are the significant predictors of purchase behavior. The findings might have some practical and theoretical values and contributions.